A complete hydatidiform mole and coexisting viable fetus in a twin pregnancy: a case report with literature review. (31st December 2023) - Wang, Guan; Cui, Hongyan; Chen, Xu
Abstract: Introduction: A twin pregnancy involving a hydatidiform mole (HM) coexisting with a developing fetus is an extremely rare obstetric complication, which typically presents as a complete hydatidiform mole with a coexisting fetus (CHMCF) or a partial hydatidiform mole with a coexisting fetus (PHMCF). Case presentation: A 26-year-old woman was admitted to our hospital due to a small volume of vaginal bleeding during the 31st week of pregnancy. The patient was previously healthy, and an intrauterine singleton pregnancy was detected by ultrasound on day 46 of gestation; however, bunch-of-grapes sign was observed in the uterine cavity at 24 weeks. The patient was subsequently diagnosed with CHMCF. As the patient insisted on continuing her pregnancy, she underwent hospital monitoring. Vaginal bleeding occurred in the 33rd week again and received a course of betamethasone, then continued pregnancy after bleeding stopped spontaneously. In the 37th week, a male infant weighing 3090 g was delivered by cesarean section, with an Apgar score of 10 at 1 min and a karyotype of 46XY. Placental pathology confirmed the diagnosis of a complete hydatid tumor. Conclusion: In this report, a case of CHMCF was maintained by monitoring of blood pressure, thyroid function, human chorionic gonadotrophin, and fetal condition during pregnancy. A live newborn was delivered by cesarean section. CHMCF is a clinically rare disease with high risks; thus, it should be diagnosed carefully using several tools, including ultrasound, magnetic resonance imaging, and karyotype analysis and dynamically monitored if the patient decides to continue the pregnancy.